1.Transform the expression disappearing the root from the consequent. 1/(5)1/3-(2)1/3 (1/3 is the exponent) 2.Prove that for evry real x, y and z it's true: (x-y)3+(y-z)3+(z-x)3=3*(x-y)*(y-z)*(z-x)
Follow Math Help Forum on Facebook and Google+
Originally Posted by blertta 1.Transform the expression disappearing the root from the consequent. 1/(5)1/3-(2)1/3 (1/3 is the exponent) 2.Prove that for evry real x, y and z it's true: (x-y)3+(y-z)3+(z-x)3=3*(x-y)*(y-z)*(z-x) 2. Put x - y = m, y - z = n then z - x = -(m+n) LHS = m^3 + n^3 - (m+n)^3 = -3 (mn^2 + nm^2) = -3mn(m+n) RHS = 3mn * -(m+n) = LHS. I don't understand Q 1.
For the first problem, multiply top and bottom by . For the second problem, it's just a matter of multiplying out both sides of the expression. Use binomial expansion on the left side.
View Tag Cloud